Effect of Interrow Spacings on Growth, Yield, and Yield Components of Common Bean (Phaseolus vulgaris L.) Varieties in the Central Rift Valley of Ethiopia - Shanko Bakure; Tarekegn Yoseph; Demisie Ejigu (Advances in Agriculture)
The common bean is the crop used as food, feed, and to improve soil fertility. However, the production and productivity were affected by poor nutrition and fertilizer management, inappropriate interrow spacings, and the poor genetic makeup of the crops in Ethiopia. Hence, a study was conducted in two research stations at Arsi Negele and Melkasa Agricultural Research Center (MARC), during 2019 cropping season. The treatments consisted of three interrow spacings (30 cm, 40 cm, and 50 cm) and three common bean varieties (Dame, SER-119, and KAT-B9) combined in a factorial arrangement laid out in the field using (randomized complete block design) RCBD with three replications. Data on growth and yield parameters obtained were subjected to analysis of variance. Regarding the interaction effect, leaf area, number of seed pods−1, and grain yield were significantly influenced by the interrow spacings and common bean varieties at both locations. Plant height, number of pods plant−1, total dry biomass, leaf area index, hundred seed weight, and harvest index were significantly influenced by the interrow spacings and common bean varieties at Arsi Negele, whereas they were nonsignificant for MARC. In this study, the highest grain yields (2.23 and 2.17 tons/ha) were obtained from narrow interrow spacings (30 and 40 cm) combined with variety SER-119 at both locations. Hence, the highest net benefits (30848.7 and 29970.4 ETB) were obtained from SER-119 (30 cm × 10 cm, and 40 cm × 10 cm) at Arsi Negele and MARC, respectively. It was recommended that the narrow (30 cm) interrow spacing be used with variety SER-119 for common bean production in the study areas and similar agro-ecologies. On the other hand, the use of wider interrow spacings (40 cm or 50 cm) had a significant importance in improving hundred seed weight, seed quality, and disease incidences of common bean varieties at the given studied sites.